Evaluasi Kinerja Keuangan Daerah Berdasarkan Rasio Kemandirian, Efisiensi, Efektivitas, dan Pertumbuhan pada Daerah Istimewa Yogyakarta Tahun 2019–2024 - Reni Isuntari; Salamatun Asakdiyah (Jurnal Manajemen Riset Inovasi, 2026)
This study aims to examine the level of regional financial independence and various financial ratios in assessing the performance of regency and city governments in the Special Region of Yogyakarta (DIY) for the 2019–2024 period. The method employed is a descriptive qualitative approach supported by quantitative data in the form of Budget Realization Reports (LRA). Performance measurement was conducted through several key indicators, including independence, effectiveness, efficiency, and growth ratios. The results indicate that the level of fiscal independence remains relatively low, characterized by a high dependency on transfer funds from the central government. On the other hand, the effectiveness ratio shows good achievement, as most regions were able to meet their revenue targets, particularly from Local Own-Source Revenue (PAD). However, the efficiency of expenditure management remains uneven across regions. Furthermore, the revenue growth ratio shows fluctuations influenced by economic conditions, including the impact of the pandemic. Overall, regional financial performance still needs to be improved, especially in strengthening fiscal independence and optimizing PAD potential.